2016
DOI: 10.1111/jpr.12131
|View full text |Cite
|
Sign up to set email alerts
|

Basic Psychological Need Satisfaction and Frustration in Japan: Controlling for the Big Five Personality Traits

Abstract: Abstract:The present study investigated the function of satisfaction and frustration of the basic psychological needs -autonomy, competence, and relatedness -that contribute to subjective well-being (life-satisfaction, vitality, and depression) through a back-translation procedure of the Basic Psychological Need Satisfaction and Frustration Scale (BPNSFS). A total of 564 Japanese undergraduates (356 males, 205 females, three unknown; M age = 18.61 years, SD = 1.48) participated in a questionnaire survey. Confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
84
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 32 publications
21
84
0
7
Order By: Relevance
“…Conversely, needs frustration has a negative impact on life satisfaction and vitality and strong positive effect on depression. This point of view is further supported by Nishimura and Suzuki's () study, which investigated the effects of needs satisfaction and frustration on Japanese students' life satisfaction, vitality, and depression. The findings revealed that needs satisfaction positively enhances Japanese students' life satisfaction and negatively enhances depression, whereas needs frustration undermines life satisfaction and enhances depression.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 76%
“…Conversely, needs frustration has a negative impact on life satisfaction and vitality and strong positive effect on depression. This point of view is further supported by Nishimura and Suzuki's () study, which investigated the effects of needs satisfaction and frustration on Japanese students' life satisfaction, vitality, and depression. The findings revealed that needs satisfaction positively enhances Japanese students' life satisfaction and negatively enhances depression, whereas needs frustration undermines life satisfaction and enhances depression.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 76%
“…NS, need satisfaction; NF, need frustration; plus signs denote hypothesized positive associations, the "ø" sign denotes that no associations were expected, while minus signs denote hypothesized negative associations 16 hours a week in many countries (Fisher & Robinson, 2011). As one of the major companies, Netflix boosts around 100 million members in almost 200 counties with more than 125 million hours of TV shows being available readily (Netflix, 2017) and with 70% of its users binge-watching shows regularly (Smith, 2017). According to the data of the Pew Research Center, the percentage of adults watching series has doubled in recent years (Purcell, 2010).…”
Section: Study 1: Series Watchingmentioning
confidence: 99%
“…According to the data of the Pew Research Center, the percentage of adults watching series has doubled in recent years (Purcell, 2010). As one of the major companies, Netflix boosts around 100 million members in almost 200 counties with more than 125 million hours of TV shows being available readily (Netflix, 2017) and with 70% of its users binge-watching shows regularly (Smith, 2017). In sum, although series watching is becoming an increasingly important screen-based activity, it still has not received the attention of psychological research that it merits.…”
Section: Study 1: Series Watchingmentioning
confidence: 99%
“…sport, education, work and healthcare) and across cultures has established a clear link between basic psychological need satisfaction (BPNS) and well-being. 3,4 In older people, few studies have focused on this issue. Some of them have nevertheless shown that BPNS was positively associated with well-being indicators (e.g.…”
Section: Introductionmentioning
confidence: 99%